Usulan Rancangan Perumusan Opini Audit Internal Pada Kegiatan Audit Aparat Pengawasan Intern Pemerintah - Fadila, Ahmad; Rahadian, Yan (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. The research proposed to provide input to the Government Internal Supervisory Apparatus or Aparat Pengawasan Intern Pemerintah (APIP) on the importance of the application of internal audit opinion, analyze the perceptions of auditors, auditors, and users of the internal audit opinion opinion applied, and use the formulation of internal audit opinions in accordance with the results of APIP audit reports . Case studies use case study methods with qualitative methods. The object of research is five APIP units for audit, and one unit of research results for APIP audits. The research data was obtained from primary and secondary data through documentation and interviews. This research shows that the public sector internal audit opinion is needed to move towards APIP level 4 capability of the Internal Audit Capability (IA-CM) capability. According to auditor perceptions, internal opinion audits through the process of planning and carrying out internal audits with professional competence and accuracy, will produce a quality and objective opinion. According to the auditee's perception, the internal audit opinion is a part of the organization and an assessment of the unit's performance improvement. According to the perception of users of the report, internal audits have an influence on the decision-making process. This study proposes the identification of measurement criteria for each governance arrangement, risk management, and organizational control in the administrative field that is appropriate for public sector internal audit opinion formulation. This research also discusses opinions that are in accordance with the needs of auditors, auditors, and users of opinion reports with three or four levels, which can be applied properly at the micro or macro level. Keywords. Internal audit; public sector; internal audit opinion; APIP; IA-CM.Abstrak. Penelitian ini bertujuan untuk memberikan masukan kepada Aparat Pengawasan Intern Pemerintah (APIP) atas pentingnya penerapan opini audit internal, menganalisis persepsi auditor, auditi, dan pengguna laporan jika opini audit internal diterapkan, dan mengusulkan rancangan perumusan opini audit internal yang tepat pada laporan hasil audit APIP. Penelitian ini menggunakan pendekatan studi kasus dengan metode kualitatif. Objek penelitian adalah lima unit APIP beserta auditinya, dan satu unit pengguna laporan hasil audit APIP. Data penelitian diperoleh dari data primer dan sekunder melalui dokumentasi dan wawancara. Penelitian ini menunjukkan bahwa opini audit internal sektor publik sangat diperlukan untuk melangkah menuju kapabilitas APIP level 4 Internal Audit Capability Model (IA-CM). Menurut persepsi auditor, pemberian opini audit internal melalui proses tahapan perencanaan dan pelaksanaan audit internal dengan kompetensi dan kecermatan profesional, akan menghasilkan opini yang bermutu dan objektif. Menurut persepsi auditi, opini audit internal merupakan penilaian bagi organisasi dan membawa dampak terhadap peningkatan kinerja unit. Menurut persepsi pengguna laporan, opini audit internal memberikan pengaruh terhadap proses pengambilan keputusan. Penelitian ini mengusulkan pengidentifikasian kriteria pengukuruan untuk setiap lingkup tata kelola, manajemen risiko, dan pengendalian organisasi di pemerintahan yang sesuai bagi perumusan opini audit internal sektor publik. Penelitian ini juga mengusulkan bentuk opini yang sesuai dengan kebutuhan auditor, auditi, dan pengguna laporan berupa opini dengan tiga atau empat tingkat, yang dapat diterapkan baik di level mikro maupun makro.Kata kunci. Â Audit internal; sektor publik; opini audit internal; APIP; IA-CM.